Learning Obstacle in the Introduction to Number: A Critical Study Within Didactical Design Research Framework - Pauji, Ikbal; Suryadi, Didi; Setambah, Mohd Afifi Bin Bahurudin; Hendriyanto, Agus (Indonesian Journal of Science and Mathematics Education, 2023)
This research unveils a profound exploration of learning obstacles experienced by elementary school students in understanding the concept of numbers, particularly in recognizing numbers zero to ten, including their notations. This study employs a qualitative approach with a phenomenological design. It sheds light on students' comprehension of the meaning of numbers and numerals, identifying five types of learning obstacles: ontogenic psychological obstacles, ontogenic conceptual obstacles, ontogenic instrumental obstacles, didactical obstacles, and epistemological obstacles. Acting as the primary instrument, the researcher undertakes the entire research process using diagnostic assessments and interview guidelines, from data collection to reduction, presentation, and conclusion. The findings illustrate variations in students' understanding of the meaning and notation of numbers, with the five learning obstacles manifesting in diverse contexts. This analysis is based on students' responses to diagnostic assessments and in-depth interviews. The insights gained underscore the necessity for didactic designs that accommodate concrete aspects, emotional engagement of students, and the evaluation of instructional materials to enhance the understanding of numerical concepts. The research implications include recommendations for developing effective didactic designs to address the identified learning obstacles.